The Influence of Public Consumption and Investment on Economic Growth in Banten Province - Bado Riyono; Sumaryoto; Meirinaldi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine the influence of consumption on economic growth in Banten province, to determine the influence of investment on economic growth in Banten province and to determine the influence of consumption and investment on economic growth in Banten province together. The method used is a quantitative method. Data taken from the Central Bureau of Statistics for 2018-2022. The results of the research are that investment influences economic growth, consumption influences economic growth and investment and consumption influence economic growth together. The central and regional governments can pay attention and create regulations that make investment easier in their respective regions.